RANCANG BANGUN DAN VALIDASI ALAT UJI GETARAN UNTUK MENENTUKAN KONSTANTA PEGAS DAN KONSTANTA PEREDAMAN PADA SISTEM MASSA PEGAS TORSI SPIRAL MENGGUNAKAN METODE DINAMIS - Eiki Sulaiman Hafidz (2024)
Vibration is a movement that frequently occurs in a machine and it is a significant factor contributing to failures. This research aims to design and manufacture a vibration laboratory tool that provides insights into the properties of underdamped spiral torque springs, the influence of mass distribution on the natural frequency of the springs, and the provision of a laboratory tool for the environment of Universitas Pembangunan Veteran Jakarta. A quantitative method was employed to determine the properties of the spiral torque springs in dynamic conditions for various load distribution scenarios by allowing the springs to oscillate until reaching equilibrium. The research results indicate consistent spring property values with errors of approximately 40% for both the spring constant and damping constant when comparing each mass distribution variation. The natural frequency also varies for each load distribution condition due to changes in the moment of inertia values for each mass distribution variation.